Aristotle as a Neuroscientist: The Power of Habit and the Science of the Golden Mean - Tsagaris, Christos (Conatus - Journal of Philosophy, 2018)
Exploring habit as part of memory concerns both Aristotle and today’s neuroscience. Although the findings of the latter clearly deviate from their Aristotelian origins, today that research has reached a stalemate many suggest that research should again put back in the context of Aristotle’s reflection. The purpose of this article is to examine the two opposint views and present their overlappings, as discussed by recent literature, namely that, as many experts in the field believe, the blending of neurophysiological research with the widespread variance of Aristotelian reflection could reveal the "middle path" where relevant research will be oriented.